SISTEM INFORMASI ARKEOLOGIS - Nurhadi Rangkuti (BRIN, 2000)
Establishing an SIA with a GIS application is a challenge because it is full of obstacles. The real obstacles are the limited tools (hardware and software) and the lack of trained personnel. In addition, new equipment and systems will affect the running of an organization. To be able to carry out SIA properly requires not only investing in computers, digitizers, plotters, color printers, GIS software itself, and spatial data (maps, aerial photographs, satellite imagery), but also training managers, planners and data collectors in using the technology. With the formation of computer-based SIA, it is necessary to have a kind of